Diaryl ethers with carboxymethoxyphenacyl motif as potent HIV-1 reverse transcriptase inhibitors with improved solubility - Frączek, Tomasz (J Enzyme Inhib Med Chem, 2017)
In search of new non-nucleoside reverse transcriptase inhibitors (NNRTIs) with improved solubility, two series of novel diaryl ethers with phenacyl moiety were designed and evaluated for their HIV-1 reverse transcriptase inhibition potentials. All compounds exhibited good to excellent results with IC(50) at low micromolar to submicromolar concentrations. Two most active compounds (7e and 7 g) exhibit inhibitory potency comparable or even better than that of nevirapine and rilpivirine. Furthermore, SupT1 and CD4(+) cell infectivity assays for the most promising (7e) have confirmed its strong antiviral potential while docking studies indicate a novel binding interactions responsible for high activity.